IMPACT OF LIBRARY ANXIETY ON DIGITAL LIBRARY UTILISATION AMONG UNDERGRADUATES IN A NIGERIAN PRIVATE UNIVERSITY (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Academic libraries all over the world, especially in Nigeria have invested heavily on the provision of digital resource in order to provide current and relevant information sources for the(ir) users. This is imperative in a dynamic knowledge society where information become obsolete in the twinkle of an eye. However, there are several factors that can affect the effective Utilisation of these digital resources. This study examined the impact of library anxiety on the utilisation of digital library resources by undergraduates in a Nigerian private university. The study adopted a survey research method. The study sample was selected using stratified random sampling to select 165 undergraduate students from four faculties in the university which represents 5% of the total population (n= 3285). The data for the research was collected using a standard scale; the AQAK Library anxiety questionnaire and the analysis was done using the Statistical Package for Social Science (SPSS). Findings established that a significant number of the students (n= 67; 70%) experienced more than low anxiety based on the AQAK Scale. It was also revealed that there is a significant negative relationship (r = -0.13, p > 0.1) between library anxiety and use of digital library resources by the students; an indication that the use of digital library resources increases as library anxiety decreases in the students. The study therefore recommended that user education programs should be intensified and library staff should make more effort to develop a cordial relationship with library users in order to eliminate all forms of library anxiety.